Inhibition of STAT3 by RNA interference suppresses angiogenesis in colorectal carcinoma - W.F. Qian; W.X. Guan; Y. Gao; J.F. Tan; Z.M. Qiao; H. Huang; C.L. Xia (Brazilian Journal of Medical and Biological Research, 2011)
In order to investigate signal transduction and activation of transcription 3 (STAT3) signaling on angiogenesis in colorectal carcinoma (CRC) after inhibiting STAT3 expression, we constructed the HT-29-shSTAT3 cell line by lentivirus-mediated RNAi. Cell growth was assessed with MTT and the cell cycle distribution by flow cytometry. CRC nude mouse models were established and tumor growth was monitored periodically. On day 30, all mice were killed and tumor tissues were removed. Microvessel density (MVD) was determined according to CD34-positive staining. The expression of vascular endothelial growth factor A (VEGFA), matrix metalloproteinase-2 (MMP2) and basic fibroblast growth factor (FGF2) was monitored by quantitative real-time PCR and Western blot analysis. Knockdown of STAT3 expression significantly inhibited cell growth in HT-29 cells, with a significantly higher proportion of cells at G0/G1 (P < 0.01). Consistently, in vivo data also demonstrated that tumor growth was significantly inhibited in mice injected with HT-29-shSTAT3 cells. MVD was 9.80 ± 3.02 in the HT-29-shSTAT3 group, significantly less than that of the control group (P < 0.01). mRNA and protein levels of VEGFA and MMP2 in the HT-29-shSTAT3 group were significantly lower than in the control group (P < 0.05), but no significant difference was observed in the mRNA or protein level of FGF2 (P > 0.05). Taken together, these results demonstrate that STAT3 signaling is important to the growth of CRC and promotes angiogenesis by regulating VEGFA and MMP2 expression.